Optimizing Individual Counseling to Overcome Problems and Enhance Participation at Pesantren An-Nur 2 - Kemal Husen; Abdullah Hilmi; Ari Abdi (Universitas PGRI Sumatera Barat, 2026)
This study examines the implementation and role of counseling in addressing student issues at Pondok Annur 2 Al- Mutadlo , focusing on second-year high school (grade 11) students. The research highlights the need to evaluate counseling's effectiveness in reducing misconduct—such as smoking and low participation in Islamic boarding school activities—and improving engagement in kitab kuning learning. Using a qualitative case study approach, data were gathered through daily observations and in-depth interviews. Results show that ndividual counseling is effective in guiding students through their identity-forming stage, leading to a positive behavioral shift. The number of student smokers decreased from 12 in the first week to 2 by the third week. These findings suggest that optimizing individual counseling is essential for enhancing student well-being in the Islamic boarding school environment. Keywords: counseling, students, Islamic boarding school